Mediation of behavioural and socioeconomic risk factors associated with malaria in children in Ghana: Theresa Habermann. (25th October 2022) - Habermann, T; Lorenz, E; Puradiredja, DI
Abstract: Background and objectives: Malaria remains a major global public health concern and a leading cause of morbidity and mortality especially among children <5 years in Ghana. While an association between poverty and malaria has long been recognised, evidence on the causal pathways between socioeconomic position (SEP) and malaria is scarce. Our study contributes to addressing this gap by investigating the association whilst taking mediation through potential behavioural and socioeconomic factors into account. This can help to identify more specific targets for interventions on a structural level. Methods: Using data of 3, 004 children from the Malaria Indicator Survey of the Demographic and Health Surveys Program conducted in Ghana in 2019, a household wealth index (quintiles) was derived using principal component analysis based on household assets. Causal multiple mediation analyses investigated mediating effects of treatment-seeking, bed net (LLIN) use, educational attainment, and housing conditions on the association between socioeconomic position and children's malaria fever events. Results: Higher maternal educational attainment and housing conditions jointly mediate 18% of the association between socioeconomic position and malaria fever events (OR = 0.98; 95%CI = 0.96-0.99). Maternal educational attainment and seeking formal prenatal health care jointly mediate 20% of the total effect (OR = 0.98; 95%CI = 0.95-1.00), in presence of a lower socioeconomic position. No strong mediation was found for educational attainment jointly with the use of LLINs between malaria and socioeconomic position in this study (OR = 0.99; 95%CI = 0.97-1.01). Conclusions: As shown by the proportions mediated between malaria and socioeconomic position, findings suggest that current malaria control efforts could be strengthened by investments at the structural levels, such as increased (female) education, targeted improvements in housing, and stronger integration of informal health care. Key messages: Mediation analysis highlights possible targets for structural malaria interventions, as educational improvements, housing and health care provider mediate up to 20% between SEP and malaria. Structural interventions should include improving housing conditions, quality education for women and the inclusion of informal health care provider for preventive actions against malaria.